Factors influencing zakah on business compliance behavior among sole proprietors in Saudi Arabia - Hamdan, Alosaimi Mushari (2016)
Zakah is a financial worship imposed by Allah (SWT), and it is considered within Muslims’ communities a major source for funding the poor and needy. However, the amount of zakah collected from businesses in Saudi Arabia is not satisfactory, nor is the level of compliance among sole proprietors. The main objective of this study is to investigate the factors that influence zakah business compliance behavior. The research framework was developed based on the theory of planned behavior (TPB), predominating factors in deterrence theory, and fairness from equity theory, as well as guided by past studies. Partial least squares structural equation modeling was used for relationships analysis. The questionnaires were distributed to survey sole proprietors in Saudi Arabia. Several statistical techniques for data analysis were used. The results of this study confirm the applicability of the TPB in the context of zakah on business in Saudi Arabia, more specifically suggesting that compliance intention and penalty magnitude predict compliance behavior significantly. Moreover, fairness, attitude, subjective norms, and penalty magnitude are significant predictors of compliance behavior through the compliance intention. Besides, business peers and religious leaders were found to be significant referent groups. Moreover, the influences of fairness and subjective norms on compliance intention were partially mediated by attitude. In addition, the zakah system’s perceived fairness was found to be multidimensional, consisting of eight dimensions. However, the detection risk found in this study insignificant. Overall, the model shows the significance of integrating audits and penalties perceptions with fairness, attitude, and norms in explaining and predicting zakah on business compliance behavior, which would be a guide for a successive compliance strategy that zakah authorities could implement. Implications for the literature and practice were discussed, and the limitations pertaining to the study outcome and suggestions for future research were discussed as well.